Abnormal differentiation of intestinal epithelium and intestinal barrier dysfunction in diabetic mice associated with depressed Notch/NICD transduction in Notch/Hes1 signal pathway. (6th June 2014) - Min, Xiao‐Hui; Yu, Tao; Qing, Qing; Yuan, Yu‐Hong; Zhong, Wa; Chen, Guang‐Cheng; Zhao, Li‐Na; Deng, Na; Zhang, Li‐Fa; Chen, Qi‐Kui
Abstract Proliferative change and intestinal barrier dysfunction in intestinal mucosa of diabetes have been described, but the differentiation characteristics of intestinal epithelial cells (IECs) and the mechanisms in the IECs development remain unclear. To explore the intestinal epithelial constitution patterns and barrier function, the diabetic mouse model was induced by streptozotocin. Tight junctions between IECs were significantly damaged and the serum level of D‐lactate was raised in diabetic mice (P < 0.05). The expression of Zo1 and Ocln in the small intestine of diabetic mice were lower, while the markers for absorptive cell (SI) and Paneth cell (Lyz1) were significantly higher than in control mice (P < 0.05). The expression of Msi1, Notch1, and Dll1 in small intestine gradually increased throughout the course of hyperglycemia in diabetic mice (P < 0.05). However, the expression of NICD, RBP‐jκ, Math1, and Hes1 had a reverse trend compared with Msi1 and Notch1. Intestinal absorptive cells and Paneth cells had a high proliferation rate in diabetic mice. However, the intestinal barrier dysfunction associated with the decreased expressions of Zo1 and Ocln was detected throughout hyperglycemia. In conclusion, downregulation of Notch/Hes1 signal pathway caused by depressed Notch/NICD transduction is associated with the abnormal differentiation of IECs and intestinal barrier dysfunction in diabetic mice.